Comparison of Aesthetic Plastic Surgery Laws Applied in the United States and Indonesia - Endang Sri Sarastri; Liliana Tedjo Saputro; MC Inge Hartini (LAW REFORM, 2021)
Advances in science and technology in the field of aesthetic plastic surgery today no longer aims to treat but is used to change a person in supporting his appearance. The authority to carry out these medical procedures belongs to the Reconstructive and Aesthetic Plastic Surgeon Specialist (Dr. SpBP-RE), but the results of the medical actions carried out by Dr. SpBP-RE are not necessarily in accordance with the wishes of the patients. In order to avoid disputes between Dr. SpBP-RE and its patients and how to deal with it, the laws that apply in every country in the field of medicine, especially aesthetic plastic surgery, must be clear and firm. This study aims to find out and analyze the laws that apply in the field of aesthetic plastic surgery in Indonesia and in the United States so that the results can be theoretically and practically useful in overcoming medical malpractice. The type of research used was "juridical normative" research, and the analysis of legal materials was carried out qualitatively using descriptive analytical and prescriptive methods. The author compared the legal relationship between Dr. SpBP-RE and its patients, the efforts to handle medical malpractice, and proved and negated it in the field of aesthetic plastic surgery in legal proceedings in the United States and Indonesia. It is expected that Indonesia can learn from the countries that have succeeded in dealing with medical malpractice in the field of plastic surgery.